Textbook of Contact Dermatitis - Rycroft, Richard J. G.; Menné, Torkil; Frosch, Peter J. (Springer Berlin Heidelberg, 1995)
10. 1. 1. 1 The Purpose of Patch Testing Patch testing is a well-established method of diagnosing allergic contact dermatitis, a delayed type of hypersensitivity (type IV reaction). Patients with a history and clinical picture of contact dermatitis are reexposed to the suspected allergens under controlled conditions to verify the diagnosis. Besides testing patients with hand, arm, face or leg eczema (stasis dermatitis), testing of other types of eczema (atopic, seborrhoeic dermatitis, nummular eczema) is sometimes indicated, especially when the dermatologist suspects contact allergy to prescribed topical medicaments and their vehicles. Apart from its use to confirm a suspected allergic contact dermatitis, the patch test procedure can also be used before recommending alternative corti costeroids, skin care products, cosmetics, gloves, etc. in a particular patient. If the patient does not react to the alternatives tested, it is very unlikely that she or he will react to the products in ordinary use. 10. 1. 1.2 Standardization The first patch tests according to present principles were carried out in 1895 [1], but were preceded by some preliminary experiments [2] (see Chap. 1)